Oropharyngeal Cancer Squamous Cell Carcinoma. Our experience and review of the literature - Doménech Máñez, Iván (2021)
Objectives: to evaluate the epidemiological and clinical characteristics of patients with oropharyngeal cancer squamous cell carcinoma (OPSCC) in our series and to compare them with the literature. Patients And Methods: We present an observational, prospective and non-randomized study, in which we include 38 patients diagnosed with OPSCC in our center over 5 years (2016-2020). Results: Out of 168 patients with head and neck carcinoma, the 22.6% were diagnosed with OPSCC and the 31.6% with HPV. This subgroup is characterized for being patients younger than 59.1 years old, consuming less alcohol and/or tobacco and presenting carcinoma more frequently in the tonsil. Conclusions: The OPSCC has increased in the past years, showing an increment in those associated with HPV. Our HPV positive patients have been diagnosed at an early stage, they were younger, healthier and additionally, had a better life expectancy.